The Usage of Scriptural Nativity Motifs in Early Greek and Slavonic Hymnography - Santos Marinas, Enrique (Studia Ceranea, 2023)
In this article I will make a survey of the usage of the main nativity motifs that can be found in early Greek and Slavonic hymnography, such as the kata stichon hymns. Moreover, I will compare them with the nativity motifs that are mentioned in several works belonging to the homiletic literature, such as Pseudo-Chrysostom’s sermon known as In illud, Memor fui Dei, et delectatus sum or St. Proclus’ Oratio in natalem diem Domini, as well as with the apocryphal Gospels and Infancy Gospels. In this way, we can have an idea of the mutual references that are made between all those works, and of the different usage that they show.